2020
DOI: 10.47489/p000s344z764mc
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Occult Hepatitis B in Pregnant Women Attending Antenatal Care Unit of a Tertiary Care Hospital

Abstract: Introduction: Occult infections (OBIs) caused by hepatitis B virus (HBV) are detected by the presence of HBV DNA without surface antigens. The prevalence of HBsAg in general population of Pakistan is around 3%, but there is no data regarding the occurrence of OBIs. Aims & Objectives: The goal of this research was to assess the frequency of occult hepatitis B infection in pregnant females presenting to antenatal care unit of Shaikh Zayed Hospital, Lahore. Place and duration of study: These samples were hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…15 Our data showed that the frequency of positive total HBc Ab in the studied cases was 4.2%, and the frequency was statistically significantly increased in unvaccinated group when compared to the vaccinated group. Our results are consistent with those reported by Mbangiwa et al, 2018, 16 and Ali et al, 2020, 17 they found that the prevalence of OBI in was 6•6% and 5% in pregnant women, respectively. Moreover, Chang et al, 2010 14 also reported an increase in frequency of OBI cases among pregnant women which could be explained by immunosuppressive status of pregnancy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…15 Our data showed that the frequency of positive total HBc Ab in the studied cases was 4.2%, and the frequency was statistically significantly increased in unvaccinated group when compared to the vaccinated group. Our results are consistent with those reported by Mbangiwa et al, 2018, 16 and Ali et al, 2020, 17 they found that the prevalence of OBI in was 6•6% and 5% in pregnant women, respectively. Moreover, Chang et al, 2010 14 also reported an increase in frequency of OBI cases among pregnant women which could be explained by immunosuppressive status of pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…HBc Ab and/or HBs Ab were detected in 17•1% of pregnant women, 15•8% in the vaccinated group and 14•5% in the unvaccinated group. These findings agreed with those reported by Ali et al, 2020, 17 who found that the frequency of anti HBs was 13•2% in pregnant women and with data of Mak et al, 2020, 23 who reported that the serum markers were used to define different OBI types, which can be classified as seropositive or seronegative. In seropositive anti-HBc and/or anti-HBs were detectable in the serum.…”
Section: Discussionsupporting
confidence: 92%